Investigation of microdisk and microring lasers based on InGaAs/GaAs QWDs by the interferometry method. (December 2020) - Vinogradov, A Yu; Moiseev, E I; Kryzhanovskaya, N V; Fominykh, N A; Zubov, F I; Kulagina, M M; Mintairov, S A; Kalyuzhnyi, N A; Maximov, M V; Zhukov, A E
Abstract: The scanning interferometer method is used to measure the line width of microdisk and microring lasers with a diameter of the resonator ranging from 15 to 50 μm and active area based on InGaAs/GaAs quantum well-dots. Above the threshold, the spectral width of the line did not exceed 3 pm for all samples under study.